Zmienność termicznych pór roku w Poznaniu - Szyga-Pluta, Katarzyna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2011)
On the basis of period 1921–2008 series of monthly values of air temperature in Poznań the eight thermal seasons were characterized. The duration of thermal season was determined in relation to the day, when the air temperature crossed the following thermal thresholds: 0, 5, 10 and 15°C. Considering the values of the mean air temperature there were defined the following thermal seasons: early spring (0,0–4,9°C), spring (5,0–9,9°C), early summer (10,0–14,9°C), summer (above 15,0°C), early autumn (10,0–14,9°C), autumn (5,0–9,9°C), early winter (0,0–4,9°C) and winter (below 0,0°C). Gumiński method was applied to estimate the first and the last days and the duration of thermal periods mentioned above. It has been stated that in the analyzed period the highest range of the beginning was characteristic for early spring (Tab. 1). The lowest range characterizes the thermal autumn. Thermal summer is the longest and spring is the shortest season of the year in Poznań (Tab. 2). Thermal seasons in the warm period (the increase of temperature) began earlier in the examined period, while thermal seasons in the cold period (the decrease of temperature) tend to begin later (Fig. 1A–8A). Early spring and winter show the biggest variability of the beginning dates, while thermal autumn – the lowest one. The dates of the beginning and end of the intensive vegetation periods: early and late summer are the most stable. The greatest changeability of the length characterizes thermal winter and the lowest – late summer. Early spring tend to be shorter in the analyzed period in Poznań (Fig. 1B-8B). Longer are getting spring, summer, autumn and early winter. There were 7 years without thermal winter observed in Poznań (tab. 3), which occurred in the last twenty years of the examined period.
Keywords: Thermal seasons; Poznań